2020
DOI: 10.1039/c9se00704k
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of a noble metal free Ni(OH)2 co-catalyst and a ternary ZnIn2S4/g-C3N4 heterojunction for enhanced visible light photocatalytic hydrogen evolution

Abstract: A plausible reaction mechanism for photocatalytic hydrogen production by employing a ZnIn2S4/g-C3N4@Ni(OH)2 heterojunction photocatalyst under visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…65-2023). [35][36][37] The characteristic peaks of TCN were found at around 13.1°and 27.4°, which are associated with the (100) in-planar repeated units and (002) stacking layered structure, respectively. 38 The ZIS/TCN-3 composite displayed the characteristic signals of ZIS and TCN, Scheme 1 Schematic illustration of the synthesis process of ZIS/TCN heterojunctions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…65-2023). [35][36][37] The characteristic peaks of TCN were found at around 13.1°and 27.4°, which are associated with the (100) in-planar repeated units and (002) stacking layered structure, respectively. 38 The ZIS/TCN-3 composite displayed the characteristic signals of ZIS and TCN, Scheme 1 Schematic illustration of the synthesis process of ZIS/TCN heterojunctions.…”
Section: Resultsmentioning
confidence: 99%
“…For ZIS, the adsorption bands at 1613 and 1415 cm −1 correspond to surface-adsorbed H 2 O molecules and hydroxyl groups, respectively. 31,36 The broad peaks between 2900 and 3200 cm −1 in the TCN spectrum were ascribed to the N-H and O-H bands, associated with the terminations and absorbed H 2 O molecules, respectively. The peaks in the region of 1200-1650 cm −1 belong to the characteristic stretching vibration of C-N heterocycles.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…23 Following this work, hydroxides such as Ni(OH) 2 and Co(OH) 2 have been widely applied as cocatalysts for photocatalytic H 2 production by coupling with proper narrow band gap semiconductors including CdS, g-C 3 N 4 , and ZnIn 2 S 4 . [24][25][26][27][28][29] These works have well demonstrated that the hydroxides are capable of being alternatives for noble metal cocatalysts, and deserve more and further attention in photocatalytic H 2 production. Especially, the deepening of the knowledge of photogenerated charge transfer, capture, and active sites for H 2 production would be helpful for the design and optimization of hydroxide-modied photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular hydrogen (H 2 ) is considered as the most precious renewable and environment-friendly fuel due to the fact that it has high energy density and produces water as a by-product. [1][2][3][4][5][6][7] Visible light semiconductor-mediated photocatalytic water splitting is an inexpensive and environment friendly procedure for H 2 generation. [8][9][10][11][12] However, the use of expensive Pt as cocatalyst to bring down the overpotential of water splitting reaction raises the cost-related concerns for commercial applications.…”
Section: Introductionmentioning
confidence: 99%